2019
DOI: 10.1111/hepr.13425
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 drug pipelines in the treatment of non‐alcoholic steatohepatitis

Abstract: Non‐alcoholic steatohepatitis (NASH), which is a more severe form of non‐alcoholic fatty liver disease, can at least partly lead to cirrhosis, hepatocellular carcinoma, and hepatic failure. Liver transplantation is the only option for NASH cirrhosis at this time. By 2020, NASH is projected to overtake hepatitis C as the leading cause of liver transplants in the USA. There are still no approved drugs for treating NASH. Although there are approximately 196 agents of investigational NASH therapies in various stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 30 publications
0
39
0
1
Order By: Relevance
“…Thus, it is important to identify a potential drug and further clarify its treatment mechanism and determine its therapeutic window for ALF. In this study, we showed that selonsertib, a selective inhibitor of ASK1 and currently in a phase III clinical trial on NASH [20], could effectively protect against LPS/GalN-induced ALF by inhibiting the activation of hepatic ASK1-JNK-DRP1 pathway and alleviating mitochondrial damage of macrophages. Unfortunately, selonsertib is only effective early after LPS/GalN administration and the limited therapeutic window may be related to the time point of JNK and DRP1 mitochondrial translocation.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, it is important to identify a potential drug and further clarify its treatment mechanism and determine its therapeutic window for ALF. In this study, we showed that selonsertib, a selective inhibitor of ASK1 and currently in a phase III clinical trial on NASH [20], could effectively protect against LPS/GalN-induced ALF by inhibiting the activation of hepatic ASK1-JNK-DRP1 pathway and alleviating mitochondrial damage of macrophages. Unfortunately, selonsertib is only effective early after LPS/GalN administration and the limited therapeutic window may be related to the time point of JNK and DRP1 mitochondrial translocation.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, no approved treatments exist for NASH. Therefore, research is ongoing to identify new targets to develop safer and more effective anti-obesity and anti-NASH drugs by improving energy metabolism, insulin sensitivity and inflammation [53][54][55][56][72][73][74][75][76][77][78][79].…”
Section: Obesity Insulin Resistance and Naflmentioning
confidence: 99%
“…diabetic retinopathy or nephropathy in patients with T2DM [35]. Being a highly prevalent disease without a standard noninvasive biomarker and an approved treatment renders ΝAFLD/MAFLD/DAFLD an attractive topic for researchers, clinicians, policymakers and industry [26]; it has been estimated that the drug market for NASH will reach $US 25 billion in the USA, Japan, and European Union-5 (England, France, Germany, Italy and Spain) in 2026 [36]. This has resulted in a race to develop the most appropriate medication(s) the soonest possible.…”
Section: Future Directionsmentioning
confidence: 99%